The Employees’ Quality of Services based on The Balinese Local Wisdoms at Non Star-rated Hotels in Bali - Astina, I Nyoman Gede; Bendesa, I Komang Gde; Wiranatha, Agung Suryawan (E-Journal of Tourism, 2017)
Indonesia is classified as a country that is still promoting traditional culture in seeing service as a profession and business, including in Bali as part of Indonesian territory. Based on empirical studies about the cultural-based service quality, as well as the expectations of tourists to interact with the local knowledge has inspired a new idea to conduct a study on the quality of local wisdom-based services at the non-star hotels in Bali. The problems in this research are what factors that could explain the quality of services of employees based on the Balinese local wisdom at the non-star hotels in Bali. The result of the research showed that variables of local wisdom-based quality of service that play the most important roles are jemet (industrious), tresna (loving), asih (affectionate), and bakti (devotion) or the teaching of the Catur Sewaka which is part of the Sad Sewaka. These four factors are the positive characteristics of the Balinese which are applied in everyday life from generation to generation.
Keywords: employees' quality of service and the Balinese local wisdom.